1992
DOI: 10.1130/spe272-p191
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, compositional and rheological constraints on the origin of zoning in the Criffell pluton, Scotland

Abstract: The Criffell pluton in southwestern Scotland (397 Ma, a Newer Granite of late Caledonian age) is concentrically zoned with outer granodiorites of typically I-type aspect passing into inner granite with more evolved characteristics. The zonation is examined in terms of the compositional surfaces of bulk parameters such as Si0 2 and Rb/Sr and compositional variation is best modelled as multi-pulse, there being greater variation in bulk composition between pulses than within pulse. Published variations in Sr, Nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…In many cases, they are zoned with S-type interiors and I-type outer margins and contain mafic enclaves throughout (e.g. the Criffel pluton (Stephens & Halliday 1984;Stephens 1992)). The Trans-Suture Suite was emplaced on both sides of the Iapetus Suture, was coincident with Acadian orogenic deformation in Britain and Ireland, and post-dates an episode of transtension that followed the Caledonian Orogeny between 410 and 400 Ma (Dewey & Strachan 2003).…”
Section: Newer Granitesmentioning
confidence: 99%
“…In many cases, they are zoned with S-type interiors and I-type outer margins and contain mafic enclaves throughout (e.g. the Criffel pluton (Stephens & Halliday 1984;Stephens 1992)). The Trans-Suture Suite was emplaced on both sides of the Iapetus Suture, was coincident with Acadian orogenic deformation in Britain and Ireland, and post-dates an episode of transtension that followed the Caledonian Orogeny between 410 and 400 Ma (Dewey & Strachan 2003).…”
Section: Newer Granitesmentioning
confidence: 99%
“…Corrioux (1987) suggested that the formation of a foliation in the 151 outer zone of the pluton resulted from the later intrusion of the inner zones, providing 152 evidence for at least two stages of emplacement. WR isotopic variations and discontinuous 153 compositional zones (Stephens et al 1985;Stephens, 1992) provide further evidence for 154 multiple sources and emplacement episodes. Mafic enclaves are a conspicuous feature of 155 zones 1, 2 and 3; they are isotopically distinct from their host rocks, indicating that they are 156 not the product of crystal settling but instead represent different magmas whose relationship 157 to the WR compositions of the granitic rocks remains unclear (Holden et al 1987;Holden, 158 1991).…”
mentioning
confidence: 99%
“…Each of these batches may have a different chemistry, due to local differences in source rock, differences in the melting time and regime, and accumulation history (Stephens 1992;Hobden et al 1999;Soesoo 1999;Sobolev et al 2000). The major element chemical composition of the melts generated at the different stages of partial melting can be calculated using the existing modelling packages (i.e.…”
Section: Relationship Between Tectonic Forces and Partial Melt Chemismentioning
confidence: 99%